Nonclassic congenital lipoid adrenal hyperplasia diagnosed at 17 months in a Korean boy with normal male genitalia: emphasis on pigmentation as a diagnostic clue - Hosun Bae; Min-Sun Kim; Hyojung Park; Ja-Hyun Jang; Jong-Moon Choi; Sae-Mi Lee; Sung Yoon Cho; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2020)
Congenital lipoid adrenal hyperplasia (CLAH) is one of the most fatal conditions caused by an abnormality of adrenal and gonadal steroidogenesis. CLAH results from loss-of-function mutations of the steroidogenic acute regulatory (STAR) gene; the disease manifests with electrolyte imbalances and hyperpigmentation in neonates or young infants due to adrenocortical hormone deficiencies, and 46, XY genetic male CLAH patients can be phenotypically female. Meanwhile, some patients with STAR mutations develop hyperpigmentation and mild signs of adrenal insufficiency, such as hypoglycemia, after infancy. These patients are classified as having nonclassic CLAH (NCCLAH) caused by STAR mutations that retain partial activity of STAR. We present the case of a Korean boy with normal genitalia who was diagnosed with NCCLAH. He presented with whole-body hyperpigmentation and electrolyte abnormalities, which were noted at the age of 17 months after an episode of sepsis with peritonitis. The compound heterozygous mutations p.Gly221Ser and c.653C>T in STAR were identified by targeted gene-panel sequencing. Skin hyperpigmentation should be considered an important clue for diagnosing NCCLAH.